A feasibility study of "range-extended" EXAFS measurement at the Pt L3-edge of Pt/Al2O3 in the presence of Au2O3. Issue 1 (15th November 2017) - Asakura, Hiroyuki; Kawamura, Naomi; Mizumaki, Masaichiro; Nitta, Kiyofumi; Ishii, Kenji; Hosokawa, Saburo; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract : A feasibility study of a "range-extended" EXAFS measurement was conducted on the Pt L3 -edge of Pt/Al2 O3 in the presence of Au2 O3 . Abstract : A feasibility study of a "range-extended" EXAFS measurement was conducted on the Pt L3 -edge of Pt/Al2 O3 in the presence of Au2 O3 . The Pt L3 -edge EXAFS spectrum of the Pt/Al2 O3 sample was successfully obtained without any interference at the Au L3 -edge by means of high energy resolution fluorescence detection (HERFD) of the Pt Lα1 line with a Bragg type X-ray emission analyser crystal. A newly observed significant enhancement of the EXAFS oscillation amplitude was discussed on the points of the core-hole lifetime width and X-ray energy width. We also successfully obtained reasonable physical parameters by a conventional EXAFS curve fitting on the HERFD-EXAFS data. The HERFD-EXAFS technique can broaden the scope of application of EXAFS spectroscopy for complicated samples with many different elements.